Elmer and the Flood - McKee, David (Minneapolis, MN : Andersen Press USA, 2015)
After days of being in a cave with the rest of his herd due to torrential rains, Elmer the patchwork elephant is ready for some time alone, but first he must get help to rescue Young Elephant from an island formed by flood waters.
Ages 4-9.
"First published in Great Britain in 2015."--Title page verso.
Keywords: Rain and rainfall -- Fiction; Floods -- Fiction; Elephants -- Fiction; Animals -- Fiction